Between vision and obedience : rethinking theological epistemology : theological reflections on rationality and agency with special reference to Paul Ricoeur and G.W.F. Hegel /: rethinking theological epistemology : theological reflections on rationality and agency with special reference to Paul Ricoeur and G.W.F. Hegel. (2014) - Ille, George
No abstract available